2019
DOI: 10.1038/s41598-019-48774-1
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the tissue and plasma lncRNA-peptidome to discover peptide-based cancer biomarkers

Abstract: Proteome-centric studies, although have identified numerous lncRNA-encoded polypeptides, lack differential expression analysis of lncRNA-peptidome across primary tissues, cell lines and cancer states. We established a computational-proteogenomic workflow involving re-processing of publicly available LC-MS/MS data, which facilitated the identification of tissue-specific and universally expressed (UExp) lncRNA-polypeptides across 14 primary human tissues and 11 cell lines. The utility of lncRNA-peptidome as canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…This report identi es the IGF-1 through m7G pathway as a novel regulator of miRNA function and further affects the IGF-1R to orchestrate the mitophagy after brain insults. Considering the interest in miRNA and lncRNA targets and tools in therapeutic intervention [46], our ndings could be exploited in many non-coding RNAs-related disease settings to open up new therapeutic avenues.…”
Section: Discussionmentioning
confidence: 99%
“…This report identi es the IGF-1 through m7G pathway as a novel regulator of miRNA function and further affects the IGF-1R to orchestrate the mitophagy after brain insults. Considering the interest in miRNA and lncRNA targets and tools in therapeutic intervention [46], our ndings could be exploited in many non-coding RNAs-related disease settings to open up new therapeutic avenues.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of this method include exploration of the multidimensionality of tumor cells in terms of molecular association of multi-omics levels that may lead to the identification of new molecular features, genotype to phenotype correlation, patient-stratification, and biomarker discovery. For instance, one of the applications of integrating proteomics and genomics (proteogenomic approach) includes the identification of the polypeptides encoded by long non-coding RNAs (LncRNAs) in colon and prostate tumor tissues (Chakraborty et al, 2019). In colorectal cancer, by integrating mutation, copy number, methylation, mRNA, microRNA, and proteomics datasets, Guinney et al uncovered four consensus molecular subtypes (CMSs) that are more aligned with the clinical stratification and thus may facilitate the CMS-subtype based targeted interventions (Guinney et al, 2015).…”
Section: Vertical Data Integrationmentioning
confidence: 99%
“…Lately, peptides as tumor biomarkers have attracted increasing attention in clinical cancer treatments. Chakraborty et al identified that the lncRNA translation products had a similar expression in 11 carcinoma cell lines, which showed great stability and succeeded as a general biomarker for cancer ( 50 ). Moreover, the coding peptides in other ncRNAs also function in malignant tumors.…”
Section: Introductionmentioning
confidence: 99%